The influence of different heat treatment cycles on the properties of the steels HARDOX® 500 and STRENX® 700 - Gallina, Bruno; Biehl, Luciano Volcanoglo; Medeiros, Jorge Luis Braz; Souza, José de (Revista Liberato, 2020)
The HARDOX® 500 and STRENX® 700 steels are quenched materials from hot rolling process. The HARDOX® 500 is a low alloy steel with high values of microhardness and mechanical strength, the STRENX® 700 steel is a low alloy steel structural used in applications, where low density is associated with high mechanical strength. In this work, the two steels were submitted to different heat treatments: quenched and tempering, normalization and full annealing. The effects of these heat cycles were analyzed by optical microscopy and Vickers microhardness techniques. It was concluded that in the normalization treatment, the microhardness reduction of HARDOX® was more significant than that one of STRENX®. In the quenched and tempering process, both presented higher microhardness compared to the originally produced and characterized material with higher austenitic grain refining. The HARDOX® presented an effective increase of microhardness. In the heat treatment of full annealing, the HARDOX® 500 and the STRENX® 700 steels had similar microhardness and microstructural morphology values.